Explanatory Obligations. (September 2020) - Khalifa, Kareem; Millson, Jared
Abstract: In this paper, we argue that a person is obligated to explain why p just in case she has a role-responsibility to answer the question "Why p ?". This entails that the normative force of explanatory obligations is fundamentally social. We contrast our view with other accounts of explanatory obligations or the so-called "need for explanation, " in which the aforementioned normative force is epistemic, determined by an inquirer's interests, or a combination thereof. We argue that our account outperforms these alternatives.